Stomatal Lineage Control by Developmental Program and Environmental Cues - Han, Soon-Ki; Kwak, June M.; Qi, Xingyun (Frontiers in Plant Science, 2021)
Stomata are micropores that allow plants to breathe and play a critical role in photosynthesis and nutrient uptake by regulating gas exchange and transpiration. Stomatal development, therefore, is optimized for survival and growth of the plant despite variable environmental conditions. Signaling cascades and transcriptional networks that determine the birth, proliferation, and differentiation of a stomate have been identified. These networks ensure proper stomatal patterning, density, and polarity. Environmental cues also influence stomatal development. In this review, we highlight recent findings regarding the developmental program governing cell fate and dynamics of stomatal lineage cells at the cell state- or single-cell level. We also overview the control of stomatal development by environmental cues as well as developmental plasticity associated with stomatal function and physiology. Recent advances in our understanding of stomatal development will provide a route to improving photosynthesis and water-stress resilience of crop plants in the climate change we currently face.